Sunni chauvinism and the roots of Muslim modernism - Purohit, Teena (Princeton University Press, 2023)
"Modernist Islamic thought was an intellectual movement active in the late nineteenth and early twentieth centuries that aimed at redefining the relationship between Islam and western modernity. The movement took off at a pivotal time in Muslim history, when Muslim empires were either in serious decline or vanquished, and when the British and French were asserting their power as new colonial rulers in majority Muslim societies the world over. Muslim modernists sought to define how Muslims should orient themselves in this new world. And in particular, how their Islamic beliefs and practices should be reconciled with western ideas such as secularism, women's rights, democratic representation, and western forms of education. Teena Purohit's new account of Muslim modernism is distinctive in that she seeks to highlight something that has gone unnoticed in previous accounts of the Muslim modernist story: it has had a decided Sunni bias and has been linked to calls for suppression of minority Muslim communities. Such communities, including the Shi'a, Ismailis, Ahmadis, and Bahai's, have often been disparaged in Muslim modernist thought as sectarian or deviant and thus as not fully or authentically Muslim. In this book, Purohit reveals how a succession of key Muslim modernist thinker-activists from the colonial, anti-colonial/nationalist, and post-colonial/Islamist eras shared an obsession with Muslim "unity" that implicitly relied on a Sunni majoritarian perspective. Not coincidentally, this perspective was also held by European orientalist scholars of Islam who, like the Muslim modernists, were deeply influenced by notions of sect and heresy that had their origin in Christianity. This obsession with unity and the privileging of Sunnism that went with it was found in all forms of Muslim modernism. As Purohit shows via her close examination of a series of key modernist thinkers from the late nineteenth to the late twentieth centuries, repeated calls for "reform" or "reformation" of Islam or for a rediscovery of Islam's supposedly "lost unity" inclined the Muslim modernist project as a whole towards intolerance of Muslim minorities"--